A Study of the Living Qur’an: Understanding Wasilah Among the Suluk Naqshbandiyah Congregation in Pasaman Barat - Zulfi Widia Fitri; Sugeng Wanto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
This study aims to examine in depth the interpretation and practice of Qur'anic verses related to the concept of wasilah within the spiritual life of the Naqshbandi suluk community in West Pasaman Regency. Employing the Living Qur’an approach, this research seeks to explore how the sacred text of the Qur’an is not only read and understood theoretically but also actualized in tangible ritual and spiritual experiences within the Sufi order. The main focus of this study is the community’s interpretation of two Qur’anic verses Surah Al-Mā’idah [5]:35 and Surah Al-Isrā’ [17]:57 and how the meanings of these verses are internalized and applied across various aspects of spiritual life, including in the spiritual literature used by the followers. This research adopts a qualitative methodology with a phenomenological approach, allowing the researcher to understand the subjective religious experiences of the participants. The findings reveal that wasilah is understood as a means of drawing closer to Allah through the guidance of a murshid, the practice of dhikr, and a consistent and structured journey of self-purification through suluk practices.